Unilateral radiotherapy for tonsillar cancer with multiple ipsilateral neck lymph nodes - Kim, Tae Hyun; Wu, Hong-Gyun; Ahn, Soon-Hyun; Jeong, Woo-Jin; Cha, Wonjae; Eom, Keun-Yong (Radiation oncology journal, 2024)
Purpose: For tonsillar cancer with multiple ipsilateral neck lymph nodes, the safety and efficacy of unilateral radiotherapy (RT) have long been a topic of debate. We performed retrospective analyses of patients having ipsilateral neck lymph nodes treated with unilateral RT in two tertiary referral hospitals.Material and Methods: This study accrued 29 patients who were diagnosed as well-lateralized tonsillar cancer with multiple ipsilateral neck lymph nodes and underwent unilateral RT from March 2000 to March 2020. Patients underwent treatment with one of the following options or a combination of them: induction chemotherapy, surgery, RT, and concurrent chemoradiotherapy. We analyzed the recurrence pattern and survival with special attention to contralateral neck failure. Also, treatment-related toxicities were compared with a 1:1 matched cohort of those who received bilateral RT, using propensity score matching analysis.Results: At a median follow-up of 68 months, no contralateral neck failure was observed. Five-year actuarial locoregional recurrence-free survival, distant metastasis-free survival, and overall survival were 85.6%, 91.8%, and 92.7%, respectively. Both the acute and chronic grade 2 xerostomia occurred in 10.3% of the patients. When the toxicity for unilateral RT was compared to that of bilateral RT using a propensity score-matched cohort, a significantly lower rate of acute xerostomia was observed in unilateral RT group (55.1% vs. 82.7%, p=0.002), primarily at grade 2 level (10.3% vs. 51.7%, respectively)Conclusion: The results of our study suggest that unilateral RT can be safely performed in well-lateralized tonsillar cancer patients with multiple ipsilateral neck lymph nodes.